2019
DOI: 10.4103/jfmpc.jfmpc_766_19
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestation in leprosy: A cross-sectional study of 100 cases with literature review

Abstract: Background:Leprosy is a chronic granulomatous disease of the peripheral nerve and muscle of upper respiratory tract. Consequence to the neighboring primary site, oral lesions have been seen in 20--60% of patient with leprosy mainly lepromatous leprosy. The lepromatous nodules may be infective and may lead to the spread of disease and hence require proper diagnosis.Aim:To assess oral lesion in leprosy patients. To assess the disease and the occurrence of oral lesion according to age and gender. To detect any pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…Secondly, several studies investigated the understanding of the medical and dental professionals on oral signs related to systemic diseases [ 33 ], whereas tropical infectious diseases were always ignored. Thirdly, although some oral disorders related to tropical infectious diseases have been found in clinic [ 8 , 10 , 11 ], the researchers did not investigate the understanding of this knowledge and importance among dental professionals. However, our study paid attention to such neglected aspect of tropical infectious diseases and oral health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, several studies investigated the understanding of the medical and dental professionals on oral signs related to systemic diseases [ 33 ], whereas tropical infectious diseases were always ignored. Thirdly, although some oral disorders related to tropical infectious diseases have been found in clinic [ 8 , 10 , 11 ], the researchers did not investigate the understanding of this knowledge and importance among dental professionals. However, our study paid attention to such neglected aspect of tropical infectious diseases and oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Oral-maxillofacial system has been reported to be affected by such infectious diseases, such as parasitic diseases [ 6 , 7 ], viral diseases [ 8 , 9 ], bacterial diseases [ 10 , 11 ] and fungal diseases [ 10 , 12 ]. In addition, oral adverse events of medications for tropical infectious diseases have been also reported [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Vohra et al in 2019, oral manifestations were found in 70% of patients with leprosy, though non-specific. There was also a decrease in the incidence of oral involvement in leprosy compared with older studies, which were probably due to more effective and earlier initiation of treatment 5…”
Section: Discussionmentioning
confidence: 66%
“…A study in Netherlands on approximately 1,645 drugs suggested that 20% of patients may experience dysgeusia and hypogeusia (82). Drugs that have been reported to cause taste changes include beta blockers, ACE inhibitors, calcium channel antagonists, antimicrobials, anti-inflammatory, anti convulsants, endocrine and metabolic drugs, chemotherapeutic agents and drugs for gastrointestinal disorders (83)(84)(85)(86)(87)(88)(89). Several medications may induce taste disturbances through chemical interference and their effects on taste receptors during their development and maturity and subsequently induce oral pain through CNS mechanisms such as disruption of tonic inhibitory processes (90).…”
Section: Taste Changes In Local and Systemic Pathologiesmentioning
confidence: 99%